2017
DOI: 10.1119/1.5003753
|View full text |Cite
|
Sign up to set email alerts
|

Devices that can identify positive vs. negative charge

Abstract: When your clothes come out of the dryer, covered with static, do you know whether they are positively or negatively charged? In this article, I discuss a variety of devices that can determine sign of the charge on an insulator or conductor. Purposefully, none of these methods utilize comparison with a known charge. Some of these ideas have been previously published, and I am extending them, but many are original. These demonstrations provide students and teachers with an opportunity to contrast the actual flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Therefore, by comparing the electric charge with another known object, we try to understand the type of charge. Several ideas have been published to detect the polarity of the electrical charge [4][5][6][7]. It has been shown that electronic electroscopes with different designs and which are made of inexpensive materials will be used effectively to determine the polarity of the charge [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by comparing the electric charge with another known object, we try to understand the type of charge. Several ideas have been published to detect the polarity of the electrical charge [4][5][6][7]. It has been shown that electronic electroscopes with different designs and which are made of inexpensive materials will be used effectively to determine the polarity of the charge [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%